Can Group Intelligence Help Entrepreneurs Find Better Opportunities? - Zichu, Yan (Frontiers in Psychology, 2019)
Entrepreneurial activities are becoming more and more prevalence in our social life. One of the important questions in entrepreneurship is how to find good quality entrepreneurial opportunities. Previous researches suggested that characteristics of entrepreneurs such as their prior experiences, social capitals, and professional skills may influence the consequence of entrepreneurial opportunities finding. This research will introduce a more dynamic perspective to explain the influencing factor of the entrepreneurial opportunities finding. During the decision making process, some behaviors of team members such as joint decision making and constructive controversy may help decision makers understand key issues more comprehensive and decrease the risk come from uncertainties. Besides, this research also takes the differention of industries’ environmental dynamism into consideration. Thus, we can observe the internal and external effect at the same time.